Between open and internal privatization: the Argentine educational system from 1940 through 2010 - Veronica Gottau; Mauro Carlos Moschetti (Historia Social y de la Educación, 2016)
Abstract: The educational system of Argentina has undergone a process of decentralization along with a steady growth in private schools enrolment. This complex process is usually subsumed under the general concept of ‘privatization’. We have considered it necessary to provide a deeper understanding of the multiple dimensions this process of privatization encompasses. In this article we intend to analyze and reflect upon the transformations of the Argentine educational system and to understand the specific levels and aspects where privatization has taken place. We note that the public and the private sectors seem to have experienced divergent trajectories with compromising effects in terms of equity and social cohesion. We argue that the uneasy coexistence of a deregulated independent private sector and a hyperregulated public sector is the result of a partial and inadequate implementation of a public-private partnership scheme.